2022
DOI: 10.3390/molecules27103271
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Sodium Channel Inhibition by Amiloride Addressed with THz Spectroscopy and Molecular Modeling

Abstract: THz spectroscopy is important for the study of ion channels because it directly addresses the low frequency collective motions relevant for their function. Here we used THz spectroscopy to investigate the inhibition of the epithelial sodium channel (ENaC) by its specific blocker, amiloride. Experiments were performed on A6 cells’ suspensions, which are cells overexpressing ENaC derived from Xenopus laevis kidney. THz spectra were investigated with or without amiloride. When ENaC was inhibited by amiloride, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Mutation at this position in all three subunits removes any sensitivity to amiloride blocking [75]. A recent study of the cryo-EM structure of hENaC [38,39] by THz spectroscopy, coupled with molecular modelling, confirms this as the amiloride binding site [76].…”
Section: Amiloride-binding Sitementioning
confidence: 76%
“…Mutation at this position in all three subunits removes any sensitivity to amiloride blocking [75]. A recent study of the cryo-EM structure of hENaC [38,39] by THz spectroscopy, coupled with molecular modelling, confirms this as the amiloride binding site [76].…”
Section: Amiloride-binding Sitementioning
confidence: 76%
“…In addition, the dynamical effects exerted by ligands can be accessed from simulation trajectories. Mernea et al combined terahertz (THz) spectroscopy and MD simulations and showed the binding site of an epithelial sodium channel blocker and reduced channel dynamics upon blocker binding . As more efforts poured into ion channel drug discovery from both experimental and computational approaches, the ligand-binding, modulation, mutations, and permeation pathway of ion channels will be further illuminated.…”
Section: Membrane Protein Simulationsmentioning
confidence: 99%
“…The models of the Mamb-2 complex with the heterotrimeric α-ENaC/ASIC1a/γ-ENaC and homotrimeric ASIC1a channels were built in a lipid bilayer composed of palmitoyloleoylphosphatidylcholine (POPC) molecules similar to [41] using the CHARMM-GUI [42] Membrane Builder tool [43]. To represent N-glycans at sites 368/395 and 209/497 at the ASIC1a and γ-ENac subunits, respectively, a classic pentasaccharide core composed of two N-Acetylglucosamine (GlcNAc) and three Mannose (Man) residues was used.…”
Section: Modeling Of the Mambalgin-2 Complexes With The Asic1a And α-...mentioning
confidence: 99%